Impact of the histologic grade of acute gastrointestinal graft-versus-host disease on outcomes in pediatric patients treated with allogeneic hematopoietic stem cell transplantation - Kim, Eun Sil; Kwon, Yiyoung; Choe, Yon Ho; Kim, Mi Jin; Yoo, Keon Hee (Frontiers in Medicine, 2023)
Introduction: Acute gastrointestinal graft-versus-host disease (GVHD) is a common life-threatening complication after hematopoietic stem cell transplantation (HCT). We aimed to investigate outcomes according to the clinical, endoscopic, and histologic severity of gastrointestinal GVHD in pediatric patients treated with allogeneic HCT. Methods: This retrospective cohort study included pediatric patients who underwent sufficient endoscopic histopathologic evaluation for clinically suspected acute gastrointestinal GVHD between 2010 and 2020. Results: Fifty-one patients were included (male proportion, 68.6% [35/51]; median age at HCT, 6.4 years). When the patients were classified according to the histologic severity of gastrointestinal GVHD, the severe group had an earlier onset of GVHD symptoms and a higher proportion of patients with severe clinical gastrointestinal GVHD than the mild-to-moderate and “absent” groups. In Cox proportional hazards regression analysis, the groups with more severe clinical and histologic gastrointestinal GVHD showed a higher risk of non-relapse mortality (NRM). The 5-year overall survival (OS) rates were 58.3% and 36.4% in the mild-to-moderate and histologic gastrointestinal GVHD groups, respectively (P = 0.0384). Patients with higher clinical and histologic grades of gastrointestinal GVHD showed higher cumulative incidence of NRM. Discussion: Our results demonstrated that histologic severity of gastrointestinal GVHD is a relevant factor affecting OS and NRM, and patients with mild-to-moderate or severe histologic gastrointestinal GVHD have worse outcomes than patients without histologic GVHD. These findings support the importance of assessing the histologic grade in the diagnostic evaluation of patients with clinical gastrointestinal GVHD.